9. RESEARCH ON FACTORS RELATED TO FETAL MACROSOMIA IN FULL-TERM SINGLETON BIRTHS AT A THAI NGUYEN HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: to determine association between maternal factors and fetal macrosomia in full-term singleton births.Methods: A comparative cross-sectional descriptive study on 519 women with birth weight ≥ 3.500 grams and 519 women with birth weight between 2.500 and < 3.500 grams immediately before or after at A Thai Nguyen Hospital from June 2023 to December 2023.Results: Factors associated with statistically significantly fetal macrosomia were: maternal age ≥ 35,  history of giving birth ≥ 1 times, civil servants and worker, history of giving birth to a fetal macrosomia, maternal weight > 60kg; maternal hight > 160cm, gestational diabetes mellitus.Conclusion: Gestational diabetes, maternal weight are factors that should be considered when managing pregnancy with fetal macrosomia, especially in women with a history of giving birth to fetal macrosomia.
Keywords: Fetal macrosomia; high risk pregnant; gestational diabetes mellitus